The Hidden Cost of Cosmetic Surgery/Quality of Life Before and After - Dr. Ktistaki Georgia; Mitro Rezarta (2011)
Title, Abstract, Table of Contexts, Intro and Literature Review, Methodology, Analysis Chapter, Discussion, Acknowledgements, References, Appendixes.